Use of probiotics in animal feed (Revista Sistemas de Producción Agroecológicos, 2016)
Studies in recent years, show that the use of implemented probiotics in animal diet, demonstrate an optimal increase on performance in the production of ruminants and not ruminants intended to meet high demand occurs in protein of animal origin. The implementation of the probiotics in the diet for production animals is emerging as a positive choice for the producer improving economic and productive indicators, because it enters to compete with the overuse of antibiotics which is affecting the animal productive yield and business profit. In this paper, information is collected about the use of probiotics as an alternative to optimize the zootechnical parameters with the final purpose to reduce economic losses without deteriorating the nutritional value of the final product guaranteeing at the consumer the delivery of a harmless and good quality product.
Keywords: beneficial microorganisms; microbiota; animal diet; functional food